A Hover Fly, Allograpta obliqua (Say) (Insecta: Diptera: Syrphidae) - Howard V. Weems (EDIS)
Revised! EENY-185, a 4-page fact sheet by H. V. Weems, is part of the Featured Creatures collection. Includes references. Published by the Entomology and Nematology Department, August 2004.